Integrated Security And Privacy Preservation Approach In Mobile Crowd Sensing - Pius, Owoh Nsikak (2020)
The proliferation of mobile devices such as smartphones and tablets with embedded sensors and communication features introduces a novel sensing paradigm called mobile crowd sensing (MCS). Despite its opportunities and advantages, mobile crowd sensing still faces security and privacy issues. One major issue with effectively protecting sensitive data (such as location information) of users in MCS is the inability to annotate raw readings from smartphone GPS sensor due to its inherent “on” and “off” state. Another problem is detecting malicious data at the sensing stage of MCS. A preferred method to solve the identified problem without affecting the user experience is to annotate “sensitive”, “non-sensitive” and “malicious” data automatically